THE VALUE OF ATTENDED AND UNATTENDED AUTOMATED OFFICE BLOOD PRESSURE (AOBP) IN CLINICAL PRACTICE: COMPARISON WITH CONVENTIONAL OFFICE BLOOD PRESSURE (OBP) MEASUREMENTS AND 24-HOUR. (June 2018) - Andreadis, E.; Geladari, C.; Savva, F.; Angelopoulos, E.; Georgantoni, A.; Apeiranthiti, K.; Pantikidi, E.; Papademetriou, V.
Abstract : Objective: To compare attended and unattended AOBP with conventional OBP and daytime 24-hour ABP. Design and method: We evaluated patients referred for suspected hypertension (HTN) using conventional OBP, measured by a nurse with a semi-automated oscillometric device, and by two physicians using both the oscillometric and auscultatory techniques, blinded to each other's recordings. AOBP measurements were also performed, attended and unattended by a nurse, during the 5 minutes of rest and during the following 3 BP readings. In order to examine if AOBP was subject to order effect, AOBP was performed in 60 subjects before the conventional measurements and in 86 subjects after them. 24-hour ABP monitoring was also attained. Exclusion criteria were severe systematic disease that limits survival, secondary HTN, renal dysfunction and severe heart failure. Results: A total of 146 patients were enrolled, mean age ± SD, 56 ± 12, 68 women. The mean unattended systolic AOBP was 129 ± 15 mmHg, and the mean attended AOBP was 129 ± 5 mmHg, p = 0.89 (95% CI −1.33 to 1.52). Furthermore, the value of AOBP compared to conventional BP oscillometric, measured by both the nurse and the physician, as well as to auscultatory BP measured by a physician was found to be lower (AOBP 129 ± 15 mmHg, 136 ± 17 mmHg, 135 ± 17 mmHg, 32 ± 16 mmHg, p < 0.005 for all comparisons, 95%CI 4.26 to 9.81, 5.5 to 11.1, 0.9 to 6.2, respectively). No statistically significant difference was observed among the 2 AOBP groups, p = 0.624 (95% CI −3.532 to 5.871). Moreover, there was no statistically significant difference between AOBP and daytime 24-hour ABPM (128 ± 71 and 128 ± 13 mmHg, respectively, p = 0.864 (95% CI −1.87 to 2.23). Conclusions: AOBP readings compared favorably with daytime ABPM and their values were lower than conventional OBP. Interestingly, AOBP has similar values independently of the order of AOBP measurements, underlining the usefulness of AOBP in clinical practice.